Sequencing of two mitochondrial genomes of endangered form of the Sevan trout Salmo ischchan aestivalis. Issue 2 (3rd July 2018) - Nedoluzhko, Artem V.; Simonov, Evgeniy; Rastorguev, Sergey M.; Boulygina, Eugenia S.; Sharko, Fedor S.; Tsygankova, Svetlana V.; Nguyen, Van Quan; Gabrielyan, Bardukh K.; Roubenyan, Haikaz R.; Levin, Boris A.
Abstract: The two complete mitochondrial genomes of endangered form of the Sevan trout Salmo ischchan aestivalis are published in this paper. The mitochondrial DNA (mtDNA) is 16, 677 base pairs (bp) in length and contained 13 protein-coding genes, 2 rRNA genes, and 22 tRNA genes. The overall base composition of the genome in descending order was 29.4% – C, 27.9% – A, 26.0% – T, 16.7% – G, without a significant AT bias of 53.9%.